Antioxidant potential of extracts from peels and stems of yellow-fleshed and white cassava varieties - Ekeledo, E.; Latif, S.; Abass, A.; Müller, J. (Wiley, 2021)
This study focused on the exploration of the potentials of extracting antioxidants from peels and stems of yellow‐fleshed and white cassava varieties. The effect of particle size (0.2 and 0.5 mm) and variety on the phenolic content and antioxidant activity was assessed. The peels of the yellow‐fleshed cassava variety with a particle size of 0.2 mm showed the highest phenolic content with 681.5 GAE mg 100 g−1 and antioxidant activity of 19% and 425 μM TE g−1 dry matter using DPPH and FRAP assays respectively. The stems of the white cassava with a particle size of 0.2 mm exhibited high phenolic content (442.4 GAE mg 100 g−1) and antioxidant activity of 12.8% and 234 μM TE g−1, better than the stem of the yellow‐fleshed cassava. These results indicate that phenolic and antioxidant extractions were influenced by variety, the plant parts and particle size for the antioxidant assays.